2020
DOI: 10.32479/ijeep.8345
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Among Gdp, Carbon Dioxide Emissions, Energy Consumption, and Energy Production From Oil and Gas in Saudi Arabia

Abstract: The purpose of this paper is to investigate the causal relationship among economic growth, carbon dioxide (CO 2 ) emissions, energy consumption, and energy production from oil and gas during 1990-2017. By vector autoregressive models and Granger causality Wald tests, this study suggests that there is bidirectional relationship between: Economic growth and energy consumption, economic growth and CO 2 emissions, and electricity production from gas and CO 2 emissions. Moreover, there is a unidirectional causality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…Thus, urbanization must not be considered a method for improving the economic sustainability. Algarini [15] reported that income, energy consumption, and energy production can be used for predicting CO 2 emissions. However, another study [16] revealed that urbanization must not be tagged as a negative factor in predicting CO 2 emissions since, for example, in oil-abundant economies, oil prices could lead to an acceleration in urbanization, a situation which implies a positive effect on the CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, urbanization must not be considered a method for improving the economic sustainability. Algarini [15] reported that income, energy consumption, and energy production can be used for predicting CO 2 emissions. However, another study [16] revealed that urbanization must not be tagged as a negative factor in predicting CO 2 emissions since, for example, in oil-abundant economies, oil prices could lead to an acceleration in urbanization, a situation which implies a positive effect on the CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…The first group of studies consider that urbanization damages the environment through rural population relocation to urban areas, accelerated economic growth [13], consumer behavior and transportation [14,15], energy intensity [33] and industrial development based on fossil fuels (coal) [6,7,9]. Thus, this first category of studies either excludes a discussion on the later stages of urbanization or agrees that urbanization affects the environment, no matter at which stage [16,18,26].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the concentrations of atmospheric and other gases have increased, resulting in the greenhouse effect and the acidification of ecosystems, which has caused significant losses to the construction industry, agriculture, and public facilities. Studies have shown that fossil fuels including coal, oil, and natural gas will still dominate the energy structure in the short term [7]. Therefore, the Organization for Economic Cooperation and Development (OECD) countries and China have formulated increasingly strict regulations and laws to limit gas emissions to ensure the sustainable consumption of fossil energy [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…19 : Volume of total domestic sales of desulphurized diesel (1) 40 : Average price of total crude oil exports American region (5) SA-IGAE: Tertiary Activities Global Economic Activity Indicator 20 : Volume of total domestic sales of fuel oil (1) 41 : Volume of total crude oil exports Europe region (1) : Energy Global Economic Activity Indicator 21 : Volume of total domestic sales of asphalt (1) 42 : Value of total crude oil exports Europe region (4) : Total liquid hydrocarbons production (1) 22 : Volume of total domestic sales of other oil products (1) 43 : Average price of total crude oil exports Europe region (5) : Total gas production (1) 23 : Value of domestic sales of natural gas (3) 44 : Volume of total exports of petroleum products (1) : Total crude oil production (1) 24 : Value of domestic sales of petroleum products (3) 45 : Volume of total gasoline exports (1) : Total heavy crude oil production (1) 25 : Value of domestic sales of liquefied gas (3) 46 : Volume of exports of other oil products (1) : Total light crude oil production (1) 26 : Value of domestic sales of Pemex diesel (3) 47 : Volume of petrochemical exports (6) : Total superlight crude oil production (1) 27 : Value of domestic sales of desulfurized diesel (3) 48 : Value of petrochemical exports (4) : Total crude oil production in marine regions (1) 28 : Value of domestic fuel oil sales (3) 49 : Volume of imports of petroleum products (1) : Total Southern Region Crude Oil Production (1) 29 : Value of domestic sales of asphalt (3) 50 : Volume of liquefied gas imports (1) : Total Northern Region Crude Oil Production (1) 30 : Value of domestic sales of other petroleum products (3) 51 : Volume of diesel imports (1) : Total...…”
Section: Sa-igae: Secondary Activities Global Economic Activity Indicmentioning
confidence: 99%
“…; assumptions that the DOI: https://doi.org/10.21919/remef.v15i4.497 techniques must comply to guarantee their efficiency and capacity to model economic events. The problem emerges from the fact that these methodologies have important restrictions that reduce their potential, causing the need to adapt to new tendencies in frontier studies, to reduce these deficiencies, guarantee reliable results (Ahmad and others, 2020), (Algarini, 2020), (Dabachi and others, 2020), (Esso and Keho, 2016), (Galadima and Aminu, 2019), (Sunde, 2020).…”
Section: Introductionmentioning
confidence: 99%